1990
DOI: 10.1007/bf02423503
|View full text |Cite
|
Sign up to set email alerts
|

Axotomized, adult basal forebrain neurons can innervate fetal frontal cortex grafts: A double fluorescent tracer study in the rat

Abstract: The ability of axonal regeneration of identified adult basal forebrain (BFB) neurons was examined after homotopic grafting of fetal neocortical tissue to a lesion cavity in the frontal neocortex. Using a four step experimental procedure, adult rats first received an injection of the fluorescent dye Fluoro-Gold (FG) into the sensorimotor cortex in order to label those neurons with projections to the area by retrograde axonal transport. After one week the injection area was removed by aspiration, leaving a cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 33 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Grafting cells into cerebral cortex lesion cavities has indicated that cells can survive and develop new connections. Several papers have demonstrated that developing cells can be grafted into rodent TBIs (Castro et al, 1987 , 1988 ; Girman and Golovina, 1988 ; Kolb et al, 1988 ; Sorensen et al, 1990 ). Engraftment of pluripotent stem cell-derived neural cells or even mesenchymal stem cells or bone marrow mononuclear cells into cortical lesions has also been studied in rodents (Gaillard et al, 2007 ; de Freitas et al, 2012 ; Espuny-Camacho et al, 2013 ; Tajiri et al, 2013 ; de Freitas et al, 2015 ; Michelsen et al, 2015 ).…”
Section: Molecular Regulation Of Svz Cells After Traumatic Brain Injumentioning
confidence: 99%
“…Grafting cells into cerebral cortex lesion cavities has indicated that cells can survive and develop new connections. Several papers have demonstrated that developing cells can be grafted into rodent TBIs (Castro et al, 1987 , 1988 ; Girman and Golovina, 1988 ; Kolb et al, 1988 ; Sorensen et al, 1990 ). Engraftment of pluripotent stem cell-derived neural cells or even mesenchymal stem cells or bone marrow mononuclear cells into cortical lesions has also been studied in rodents (Gaillard et al, 2007 ; de Freitas et al, 2012 ; Espuny-Camacho et al, 2013 ; Tajiri et al, 2013 ; de Freitas et al, 2015 ; Michelsen et al, 2015 ).…”
Section: Molecular Regulation Of Svz Cells After Traumatic Brain Injumentioning
confidence: 99%
“…In many examples of transplantation to the adult cortex using embryonic neurons, either as cell suspensions or as blocks of tissue, investigators have often reported afferent connections to the transplanted cells but no evidence for efferent connections back to the recipient brain (Gonzalez and Sharp, 1987;Gates et al, 2000a). Reports of the extent of efferent connectivity from the graft to recipient tissue have varied widely, from no efferent projections (Gonzalez and Sharp, 1987;Schulz et al, 1993;Grabowski et al, 1995) to sparse or moderate (Bermudez-Rattoni et al, 1987;Isacson et al, 1988;Kelche et al, 1988;Escobar et al, 1989;Sofroniew et al, 1990;Sørensen et al, 1990Sørensen et al, , 1996Fernandez-Ruiz et al, 1991;Isacson and Sofroniew, 1992;Schulz et al, 1993) to more extensive innervation of recipient target regions (Gibbs and Cotman, 1987;Guitet et al, 1994;Hernit-Grant and Macklis, 1996). Indeed, in many behavioral studies in which experimental animals did not show improvement after transplantation, investigators have concluded that the lack of functional recovery is most likely attributable to the lack of efferent projections from the transplanted neurons to appropriate recipient target sites.…”
Section: Re-formation Of Long-distance Axonal Projections To Approprimentioning
confidence: 99%
“…Neocortical neurons are organized into distinct laminae and have complex axonal projections often over great distances. Following damage to the neocortex, significant functional recovery may depend critically on whether neurons can migrate into appropriate laminar locations, integrate into the host cytoarchitecture, differentiate into the appropriate type of neuron, and then reconstruct the specific disrupted local and distant projection patterns of the damaged host neurons (6,12,13,68,70,77,78).…”
Section: Introductionmentioning
confidence: 99%